The Royal Canadian Mounted Police - Kemp, V. A. M. (Polar Record, 1934)
The Force was founded in 1873 as the North-West Mounted Police, by an Act of the Canadian Government introduced by the first Prime Minister of Canada, Sir John A. Macdonald. Since that time there have been many changes, even the name of the Force has been altered twice, and the uniform worn nowadays by a member of the Royal Canadian Mounted Police is very different from that of the old North-West Mounted Police. The nature of the work, too, has undergone many changes since the Force first took over the establishment of law and order in the north. But, one feature, the nature of its frontier work, still links it with the hectic days of '73.